Effect of the drying method and texture improvers on reconstitution behavior of yogurt powder: physical and microbiological properties - Robinson Monsalve-Atencio (Universidad de Antioquia, 2021)
BACKGROUND: One of the most used and effective preservation strategies in foods is drying. However, there are problems with the rheological properties, color, and viability of lactic acid bacteria in the yogurt once reconstituted when applying such conservation strategies.   OBJECTIVES: Determine the concentration of the type of texture improver and drying that minimizes the negative effect on the rheological, color, and microbiological properties of a reconstituted yogurt powder. METHODS: Intended to determine the texture improver which increases rheological properties of reconstituted yogurt powder, a mixture type experimental design was applied where three texture improvers were assessed; carboxymethylcellulose (CMC) (mass fraction 0 - 1), pectin (mass fraction 0 - 1), and xanthan gum (mass fraction 0 - 1). The rheological parameters; consistency index (K), flow behavior (n), viscosity at 100s-1 (η), the storage (G') and loss (G'') modules, and the phase shift angle (δ) of each of the reconstitutions were considered as design-dependent variables. Secondly, a central composite design (face-centered) was used for assessing the effectiveness of the drying (convection, spray-drying, and freeze-drying), the concentration of the texture improver (0.0 - 1.0%), and the yogurt powder concentration (8.0 - 15.0%). The above-mentioned rheological parameters, color, and viability of the lactic acid bacteria from each reconstituted yogurt powder were considered as the dependent variables. Optimization sought to match the parameters of reconstituted yogurt powder that approximated the conditions of fresh yogurt. RESULTS: The independent variables in their lineal expression and some interactions between them had statistically significant differences (p < 0.05). At a concentration of 10.59% with 0.03% xanthan gum, the reconstitution of freeze-dried yogurt powder was the optimized condition (p < 0.05) and obtained the rheological, color, and microbiological parameters closest to fresh yogurt. CONCLUSIONS: The drying of the yogurt by freeze-drying mixed with xanthan gum as a texture improver allowed to obtain a reconstituted yogurt with properties close to the fresh product for direct consumption.